TEACHERS’ STRATEGIES IN CONDUCTING SPEAKING ASSESSMENTS FOR YOUNG ENGLISH LEARNERS AT MIS NURUL HUDA, TANJUNG MORAWA - Rizky Evionita Putri (Jurnal Warta Dharmawangsa, 2022)
ABSTRACT - The purpose of this study is to ascertain and pinpoint the teacher's comprehension of speaking, particularly for young students. Through the use of a qualitative research approach, this study tried to examine teachers' methods for administering speaking tests to young English learners. A questionnaire for expert lecturers and students, teacher interviews, and the outcomes of the most recent exam given to students make up the instrument. In MIS Nurul Huda interviews with teachers and teacher observations to evaluate young pupils' speaking abilities, a questionnaire for teachers was utilized as the testing tool. The results show that even though most teachers do not fully comprehend assessment concepts, they can nevertheless use these principles to evaluate assessments for their pupils. Despite the fact that they are unfamiliar with the assessment's terminology, their understanding of the procedure is in line with the theories advanced by the experts. The teacher employs speaking tactics for each student's speaking strengths and shortcomings throughout formative speaking assessments in the classroom. Speaking techniques include imitative speaking (repetition), intensive speaking (tasks requiring you to finish sentences and dialogues), responsive speaking (questioning and responding), interactive speaking (role playing, discussion, and conversation), and extensive speaking (illustrated discussions in stories).Keyword : Speaking Assesment, Young English, Strategies